Creeping Bentgrass, Perennial Ryegrass, and Tall Fescue Tolerance to Topramezone During Establishment. (March 2016) - Johnston, Christopher R.; Yu, Jialin; McCullough, Patrick E.
Abstract : Topramezone controls weeds in tolerant, cool-season turfgrasses, but injury potential during establishment has received limited investigation. The objectives of this research were to evaluate the tolerance of 'Penn A-4' creeping bentgrass, 'Manhattan V' perennial ryegrass, and 'Titan' tall fescue to topramezone at 18.5, 37, or 74 g ae ha −1 during establishment. Grasses were seeded in strips in October, and treatments were applied at 0, 2, 4, or 6 wk after seeding (WAS). Perennial ryegrass and tall fescue had minimal (≤ 8%) injury from all treatments, and ground cover was greater or equal to the nontreated at all application timings. Topramezone applied 4 WAS at 37 and 74 g ha −1 injured creeping bentgrass 16 and 23% at 2 wk after treatment, respectively. However, all other topramezone rates and timings caused < 10% injury. Mesotrione at 175 g ai ha −1 injured creeping bentgrass 14 to 43% at all timings and was more injurious than topramezone. Mesotrione applied at 2, 4, or 6 WAS controlled lesser swinecress ≥ 99% at 20 WAS, whereas applications on the day of seeding provided 71% control. All topramezone treatments provided poor control (< 70%) of lesser swinecress at 20 WAS. Overall, perennial ryegrass and tall fescue are tolerant to topramezone during establishment at the rates tested. Seedling creeping bentgrass has better tolerance to topramezone from 18.5 to 74 g ha −1, than to mesotrione at 175 g ha −1 and may provide end-users an HPPD inhibitor for use during establishment.